CRITICAL REVIEW OF ANALYSIS OF FINANCIAL LITERACY POLICY INTEGRATION IN THE CURRICULUM: A BIBLIOMETRIC APPROACH - Siregar, Yani Sukriah; Ria Arista Asih; Suranto (Universitas Muhammadiyah Surakarta, 2025)
This study explores the integration of financial literacy into education curricula, with a particular focus on Indonesia’s Merdeka Curriculum, using a bibliometric review of 316 peer-reviewed articles from the Scopus database (2016–2025). Through bibliometric mapping via VOSviewer, the research identifies five thematic clusters: policy development, behavioral outcomes, student knowledge and attitudes, digital financial literacy, and interdisciplinary education strategies. Key findings reveal a global surge in financial literacy research post-2016, largely driven by policy mandates and the rise of digital finance, with the United States leading in scholarly output. However, research remains heavily concentrated in high-income countries, while regions like Indonesia are underrepresented despite clear policy interest. The study uncovers several implementation barriers in educational settings, including limited teacher training, inadequate resources, and a lack of standardized evaluation metrics. Promising practices—such as project-based learning, the integration of financial literacy into mathematics, and digital tools—have demonstrated improved student engagement and financial behavior. In Indonesia, six core studies suggest a growing awareness of financial education but underscore the need for contextualized curricula and community-based support. The study recommends more inclusive policies, cross-disciplinary collaboration, and longitudinal impact assessments to ensure financial literacy becomes a core competency in global education systems.